The Perceptions of Tribun Jabar Journalists Regarding Obstacles in Covering Political News - Khoiruddin Muchtar; Ersa Devita Arditika (School of Journalism, Faculty of Communication Sciences, Universitas Padjadjaran, 2023)
The world of journalism often faces problems, especially in covering political news, but every challenge and obstacle will offer an opportunity for journalists to properly increase the value of their news. This paper aims to determine the selection and reactions of journalists from the Harian Umum Tribun Jabar in facing obstacles to covering political news. This study uses a qualitative descriptive method using primary data through observation, interviews, and documentation. The approach used in this research is qualitative. The results of the study show that first, the selection process carried out by the Morning Daily Tribun Jabar journalists is by selecting sources who are considered credible and competent in their fields so that the news will be made into interesting news. The interpretation carried out by the journalists of the Morning Daily Tribun Jabar is by reading the information obtained through the five senses, then interpreting it based on understanding and experience, then providing an assessment of the political news. Third, journalist reactions arise when there are obstacles and challenges in covering political news. Journalists are expected to be able to overcome obstacles to covering political news, so that the political information written can have a good impact on the public.